Enhancing Lubricity and Filtration Control in Water-based Drilling Fluids Using Novel Silica Nanoparticles Derived from Rice Husk Ash - Jaf, Pshtiwan T. (ARO-THE SCIENTIFIC JOURNAL OF KOYA UNIVERSITY, 2026)
The low lubricity and high filtration loss of water-based drilling fluids (WBDFs) hinder the drilling industry and are the cause of high torque and drag, while also contributing to nuisance conditions such as wellbore instability. This study presents a new, environmentally friendly SiO2 nanoparticle (NP) made from rice husk ash (RHA), one of the byproducts of agriculture, as a multifunctional additive for WBDFs. The RHA-SiO2-NPs were produced by an alkaline extraction method and characterized using X-ray diffraction and scanning electron microscopy. RHA-SiO2 NPs were incorporated (0.1–1.0 wt%) into a bentonite-based mud and evaluated for rheology, API fluid loss, and lubricity. The results showed that the addition of only 0.5 weight % RHA-SiO2 resulted in a 60% reduction in fluid loss (16.8–6.8 mL) and a 39% improvement to the lubricity coefficient (0.28–0.17) in comparison to the base fluid. The presence of the RHA-SiO2-NPs also increased the yield point and gel strengths when looking at the rheological properties, indicating improved hole-cleaning capabilities. RHA-SiO2 NPs demonstrated multifunctional performance and potential for sustainable drilling applications.